Distinct and combined impacts of climate and land use scenarios on water availability and sediment loads for a water supply reservoir in northern Morocco - Choukri, Fatiha (2020)
The objective of this study was to examine the impacts of climate and land use changes on water availability and sediment loads for a water supply reservoir in northern Morocco using data-intensive simulation models in a data-scarce region. Impacts were assessed by comparing the simulated water and sediment entering the reservoir between the future period 2031e2050 and the 1983e2010 reference period. Three scenarios of land use change and two scenarios of climate change were developed in the Tleta watershed. Simulations under current and future conditions were performed using the Soil and Water Assessment Tool (SWAT) model. The simulations showed that climate change will lead to a significant decrease in the annual water supply to the reservoir ( 16.9% and 27.5%) and in the annual volume of sediment entering the reservoir ( 7.4% and 12.6%), depending on the climate change scenarios tested. The three scenarios of land use change will lead to a moderate change in annual water inflow into the reservoir (between 6.7% and þ6.2%), while causing a significant decrease in sediment entering the reservoir ( 37% to 24%). The combined impacts of climate and land use changes will cause a reduction in annual water availability ( 9.9% to 33.3%) and sediment supplies ( 28.7% to 45.8%). As a result, the lifetime of the reservoir will be extended, but at the same time, the risk of water shortages will increase, especially from July to March. Therefore, alternative water resources must be considered.